Regional institutions in Europe and Southeast Asia: Lessons for economic integration in South Asia - Falendra Kumar Sudan (Asian Development Bank Institute (ADBI), 2020)
Except for the history of colonialism, the European Union (EU) and the Association of Southeast Asian Nations (ASEAN) have similar roots and they share initial targets to foster economic growth and competitiveness. However, the EU and ASEAN have diverging economic integration paths. The ASEAN Way implies non-interference in the internal affairs of the member nations. ASEAN has deliberately avoided creating a strong supranational regional institution and it has also avoided a strong EU-type agency. ASEAN is a major economic bloc, but compared to ASEAN, the EU is a stronger and more successful regional organization. Following profound integration initiatives in Southeast Asian countries, this region has now become the most dynamic and fastest growing regions of the world, especially when compared to other Asian subregions such as South Asia. In Southeast Asia, intra-regional trade has increased to 25% in the 2010s from 18% of total trade in the early-1990s. Southeast Asia has also become an attractive destination for foreign direct investment, which stood at 20% of total investment today compared to 12% in the early-1990s. Compared to Southeast Asia, South Asia has an abysmal performance in intra-regional trade and bilateral trade is throttled between India and Pakistan. Therefore, there is a need to harness the potential of regional cooperation through promoting regional institutions by learning from the experiences of EU and ASEAN to address the challenges faced by South Asia.
Keywords: E02; F15; F36; N73; N75; O43; 330; economic integration; regional institutions; Southeast Asia; Europe; South Asia